ANALISIS LITERATUR: MUTU PENDIDIKAN ISLAM DITINJAU DARI PRAKTIK DUALISME PENDIDIKAN NASIONAL - Rizal, Muhammad; Iskandar, Iskandar; Suryadi, Ahmad (Jurnal Dedikasi Pendidikan, 2024)
This article investigates the quality of Islamic education in the practice of dualism in Indonesia. This dichotomy is related to differences in the quality of Islamic education, as well as its implications for graduates of Islamic education institutions in the field. Through literature research, it shows that dualism in the management and implementation of Islamic education in Indonesia creates significant challenges, including non-uniformity in educational standards, an imbalance between religious education and general knowledge, as well as gaps in the quality of education between institutions. However, this article also identifies efforts to overcome this dualism, such as curriculum integration programs and capacity building for education managers. By analyzing quality in the dualistic dynamics of Islamic education management, this article provides valuable insight for education stakeholders, including the government, educational institutions, and the wider community, to develop a more holistic and integrated strategy in improving the quality and relevance of Islamic education in Indonesia